Hope for Justice and Power : Broad-based Community Organizing in the Texas Industrial Areas Foundation - Staudt, Kathleen (Book collections on Project MUSE., 2020)
"Book is a history of the Industrial Areas Foundation branch in Texas. The Industrial Areas Foundation was founded by Saul Alinsky in Chicago in 1940 and is currently an international advocacy group. The Texas branch has many affiliates throughout the state. This book describes the evolution of those affiliates and their cooperative activities with other advocacy groups"--